2021
DOI: 10.4103/jfmpc.jfmpc_2401_20
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in the Kingdom of Bahrain

Abstract: Background and Objectives: Women can experience physical abuse, mental, sexual abuse, or even controlling behavior throughout their partnership lifecycle, which must be prevented and curtailed at the early stages. Therefore, this study explores intimate partner violence (IPV) prevalence among Bahraini women, predictors of IPV, and reliability of the Women Abuse Screening Tool (WAST) questionnaire in IPV against women. Methods: The current prospective cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regarding women aged 15 years and older who experienced physical or sexual violence from an intimate partner, the data indicate that Palestine and Iran's women experienced the highest rates of violence at 17.1 and 15.2 %, respectively in 2018 (SDG, 2022). Although there is no reliable data on this for most of the countries in the region, some evidence showed that 42-58 % of women in the MENA region experience IPV (Al Ubaidi et al, 2021). While some countries have laws prohibiting violence against women, there is a noted gap in laws regarding marital rape (Danon & Collins, 2020).…”
Section: Gender Inequality In the Mena Regionmentioning
confidence: 99%
“…Regarding women aged 15 years and older who experienced physical or sexual violence from an intimate partner, the data indicate that Palestine and Iran's women experienced the highest rates of violence at 17.1 and 15.2 %, respectively in 2018 (SDG, 2022). Although there is no reliable data on this for most of the countries in the region, some evidence showed that 42-58 % of women in the MENA region experience IPV (Al Ubaidi et al, 2021). While some countries have laws prohibiting violence against women, there is a noted gap in laws regarding marital rape (Danon & Collins, 2020).…”
Section: Gender Inequality In the Mena Regionmentioning
confidence: 99%